Coapplication of Effective Microorganisms and Nanomagnesium Boosts the Agronomic, Physio-Biochemical, Osmolytes, and Antioxidants Defenses Against Salt Stress in Ipomoea batatas - Abd El-Mageed, Taia A.; Gyushi, Mohammed A. H.; Hemida, Khaulood A.; El-Saadony, Mohamed T.; Abd El-Mageed, Shimaa A.; Abdalla, Hanan; AbuQamar, Synan F.; El-Tarabily, Khaled A.; Abdelkhalik, Abdelsattar (Frontiers in Plant Science, 2022)
The application of bio- and nano-fertilizers are undoubtedly opening new sustainable approaches towards enhancing abiotic stress tolerance in crops. In the current study, we evaluated the application of effective microorganisms (EMs) of five groups belonging to photosynthetic bacteria, lactic acid bacteria, yeast, actinobacteria and fermenting fungi combined with magnesium oxide (MgO) nanoparticles (MgO-NP) on the growth and productivity of sweet potato plants grown in salt-affected soils. In two field experiments carried out in 2020 and 2021, we tested the impacts of EMs using two treatments (with vs. without EMs as soil drench) coupled with three foliar applications of MgO-NP (0, 50 and 100 μg mal-1of MgO, representing MgO-NP0, MgO-NP50 and MgO-NP100, respectively). In our efforts to investigate the EMs:Mg-NP effects, the performance (growth and yield), nutrient acquisition, and physio-biochemical attributes of sweet potato grown in salt-affected soil (7.56 dS m−1) were assessed. Our results revealed that salinity stress significantly reduced the growth parameters, yield traits, photosynthetic pigments content (chlorophyll a and b, and carotenoids), cell membrane stability, relative water content, and nutrient acquisition of sweet potato. However, the EMs+ and/or Mg-NP-treated plants showed high tolerance to salt stress, specifically with a relatively superior increase when any of the biostimulants were combined. The application of EMs and/or Mg-NP improved osmotic stress tolerance by increasing the relative water content and mebrane integrity. These positive response owed to increased the osmolytes level (proline, free amino acids, soluble sugars) and antioxidative compounds (non-enzymatic concentration, enzymatic activities, phenolic acid and carotenoids). We also noticed that soil salinity significantly increased the Na+ content, whereas Ems+ and/or Mg-NP-treated plants exhibited lower Na+ concentration, and increased K+ concentration and K+/Na+ ratio. These improvments contributed to increasing the photosynthetic pigments, growth, and yield under salinity stress. The integrative application of EMs and Mg-NP showed higher efficacy bypassing all single treatments. Our findings indicate the potential of coapplying EMs and Mg-NP for future use in attenuating salt-induced damage beneficially promoting crop performance.